Control of traction drive with PMSM from viewpoint of EMI - Doleček, Radovan; Černý, Ondřej (Univerzita Pardubice, 2010)
The paper deals with the EMI problems of the individual traction drive of tram wheel. The drive utilizes permanent magnet synchronous motor (PMSM). Until now the major attention has been paid to the control methods of this drive. Nowadays when these control methods are mastered the consideration is focused particularly on interference of designed converter of this drive to near-field environment in which are located other devices. The particular working modes of drive and their interference are demonstrated in this paper. Findings will lead to next steps for reducing of this interference which can bring about fault state of device.
Keywords: drive; motor; interference; measurement; near-field; EMI